Performance comparison between PWM and MPPT charge controllers (2019)
Charge controllers are implemented in several electronic systems to protect and control the charge and discharge rates of a battery; for off-grid Photovoltaic (PV) systems, there are two types of technologies, Pulse Width Modulation (PWM) and Maximum Power Point Tracking (MPPT). In this work, we compared two charge controllers in PV systems with the same technical specifications in order to determine the behavior of each of them under similar environmental conditions. The implementation of both charge controllers was based on firmware and hardware with original designs, using PWM and MPPT technologies. Both PV systems are composed of the charge controller, a 30 W solar panel and a 12 V – 18 Ah battery; in the experimental tests we measured the voltage and current in the panel and the battery in charge and discharge processes, observing that the MPPT controller has a higher average efficiency than the PWM controller, elucidating that the type of technology used in the charge controller has a direct impact on the efficiency, even under unfavorable conditions of solar radiation and environmental temperature. The PWM controller is an option of acceptable efficiency and lower price in relation to the MPPT controller. In the implementation of both controllers we calculated similar periods of autonomy.